2023
DOI: 10.1186/s12891-023-06265-5
|View full text |Cite
|
Sign up to set email alerts
|

The clinical necessity of a distal forearm DEXA scan for predicting distal radius fracture in elderly females: a retrospective case-control study

Abstract: Background Recent studies have demonstrated that the distal forearm dual-energy X-ray absorptiometry (DEXA) scan might be a better method for screening bone mineral density (BMD) and the risk of a distal forearm fracture, compared with a central DEXA scan. Therefore, the purpose of this study was to determine the effectiveness of a distal forearm DEXA scan for predicting the occurrence of a distal radius fracture (DRF) in elderly females who were not initially diagnosed with osteoporosis after … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Additionally, both femoral neck and spine T-scores overestimated T-scores in the forearm of the fracture group [ 14 ]. Ma and colleagues further demonstrated the importance of local forearm BMD assessment with retrospective data showing patients who sustained distal radius fractures had significantly lower forearm BMD and low T-scores about the radius were a predictive risk factor for fracture, while femoral neck, hip and spine T-scores were not significant risk factors for the occurrence of distal radius fractures [ 27 ]. These studies highlight the importance of determining local forearm osteopenia and osteoporosis separate from weight-bearing locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, both femoral neck and spine T-scores overestimated T-scores in the forearm of the fracture group [ 14 ]. Ma and colleagues further demonstrated the importance of local forearm BMD assessment with retrospective data showing patients who sustained distal radius fractures had significantly lower forearm BMD and low T-scores about the radius were a predictive risk factor for fracture, while femoral neck, hip and spine T-scores were not significant risk factors for the occurrence of distal radius fractures [ 27 ]. These studies highlight the importance of determining local forearm osteopenia and osteoporosis separate from weight-bearing locations.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows a 25.9% reduction in fracture risk at any site for those screened before the standard age of 65 [ 25 , 26 ]. Screening specifically for forearm BMD is extremely beneficial as it has a much stronger odds ratio (3.98) to predict distal radius fractures than BMD from the hip (OR = 0.27) or femoral neck (OR = 0.26) [ 27 ]. Expanded screening tools could help patients receive calcium supplementation and or vitamin D, start on osteoporosis treatment, forestall further injury, or disability.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective case–control study including women aged ≥ 50 years, BMD UDforearm was better at discriminating those with distal radius fracture than BMD measured at the hip or spine [ 5 ]. The authors did note, however, that T-scores for the ultra-distal radius site were lower than those at the hip or spine.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring BMD UDforearm is quick, with a lower radiation dose [ 4 ], but more data are needed to understand how it may assist fracture prediction. BMD UDforearm has been associated with BMD at the hip and spine [ 4 , 5 ]. Additionally, individuals with distal radius fractures have been reported to have lower BMD at the hip and spine [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that DXA of the distal forearm may be a superior method for screening bone mineral density (BMD) and assessing the risk of distal forearm fractures compared to central DXA scans. Article [17] examined the medical records of 384 female patients with distal radius fractures. Their findings indicate that BMD of the distal onethird radius is more closely correlated with hip BMD than lumbar BMD (p < 0.05 in each group).…”
Section: Introductionmentioning
confidence: 99%